Meningkatkan Minat Baca Siswa Menggunakan Strategi Know Want Learned (KWL) Dengan Media Puzzle Huruf Kelas 1 Pada Mata Pelajaran Bahasa Indonesia SDN I Wantisari Kabupaten Lebak - Rina Gunawan; Ratna Dewi; Rifki Arif Nugraha (Desanta Publisher, 2023)
ABSTRACT Increase Interests Read Students By Using a strategy KWL using Media Puzzle Letter Grades 1 On Ma ta Lessons Languages Indonesia SDN I Wantisari District District Lebak province of Banten . Research is conducted is aimed to improve the quality of their learning Languages Indonesia on aspects keterampillan memebaca pemhaman students class I Program Study of Undergraduate Education Teacher School Primary in School High Teacher Training and Science Education Sheikh Mansur Based on the formula, the problem of the lack of understanding of students about Languages Indonesia , then push the author to conduct research on how the effort g uru to improve pemaha man students about studying Languages Indonesia student school basis . In this study the authors used the KWL strategy with letter puzzle media Methodology The study 's authors use the research is conducted Action Class with grooves observations to determine the extent to which the student / students understand the reading interest in teaching Languages Indonesia , especially about increasing the interest in reading . To know that all writers do the implementation of learning in class , which consists of four stages , namely Planning ( Planning Measures ), Acting ( Implementation Measures ), Observing ( Observation ), and Reflekting ( stage assessment / evaluation ). And the results of the observations were conducted teacher well . Because most major components of which have been determined in the implementation of learning has been implemented with good Results The study , from the results of learning are good , then it will be obtained the results were good as well. The results of research in tian showed that pembelaj aran Languages Indonesia through learning media puzzle experience an increase . It is can be seen through the cycle I / meetings I students learn completely new reach an average value 83,5 In cycle II there was an increase in students studying tu NTAS with the results of the average value of 90.35 The average activity of students in aspects of the seriousness and liveliness work the assignments given by the teacher in the first cycle are in the Good category and the second cycle is in the very good category. Time study is conducted of the month Juli 2023 Up to the month of September 2023 , as many as 28 students at SDN II Wantisari District Lebak . Keywords: Improve Reading Interest Students Using Media Puzzle Puzzle